Blockage of ERCC6 Alleviates Spinal Cord Injury Through Weakening Apoptosis, Inflammation, Senescence, and Oxidative Stress - Zou, Peng; Zhang, Xiaoping; Zhang, Rui; Chai, Xin; Zhao, Yuanting; Li, Erliang; Zhang, Qian; Yan, Rongbao; Yang, Junsong; Liao, Bo (Frontiers in Molecular Biosciences, 2022)
Objective: Spinal cord injury (SCI) is a devastating disease resulting in lifelong disability, but the molecular mechanism remains unclear. Our study was designed to observe the role of excision repair cross-complementing group 6 (ERCC6) following SCI and to determine the underlying mechanism. Methods: SCI mouse models and LPS-induced microglia cell models were established. ERCC6 expression was blocked by ERCC6-siRNA-carrying lentivirus. Nissl staining was utilized for detecting neuronal damage, and apoptosis was analyzed with TUNEL and western blotting (apoptotic markers). Immunofluorescence was used for measuring macrophage markers (CD68, F4/80) and astrocyte and microglia markers (GFAP and Iba-1). Pro‐inflammatory cytokines (TNF‐α, IL‐1β, IL‐6) were measured via ELISA. Senescent cells were estimated via SA-β-Gal staining as well as western blot (senescence markers p21 and p27). Oxidative stress was investigated by detecting the expression of 4-HNE, Nrf2 and Keap1 and intracellular ROS levels. Results: ERCC6 expression was remarkably up-regulated both in spinal cord of SCI mice and LPS-induced microglia cells. ERCC6 deficiency alleviated neuronal damage and apoptosis. Macrophage infiltration and inflammatory response were suppressed by si-ERCC6 treatment. Moreover, ERCC6 blockage ameliorated astrocyte and microglia activation and cell senescence in the damaged spinal cord. Excessive oxidative stress was significantly decreased by ERCC6 knockdown in SCI. Conclusion: Collectively, ERCC6 exerts crucial functions in mediating physiological processes (apoptosis, inflammation, senescence, and oxidative stress), implying that ERCC6 might act as a prospective therapeutic target against SCI.